Author Correction: Matrix-producing neutrophils populate and shield the skin (Nature, (2025), 10.1038/s41586-025-08741-5) - Vicanolo, Tommaso; Özcan, Alaz; Li, Jackson Liang Yao; Huerta-López, Carla; Ballesteros, Iván; Rubio-Ponce, Andrea; Dumitru, Andra C.; Nicolás-Ávila, Jose Ángel; Molina-Moreno, Miguel; Reyes-Gutierrez, Pablo; Johnston, Andrew D.; Martone, Catherine; et al. (Nature, 2025)
Correction to: Naturehttps://doi.org/10.1038/s41586-025-08741-5 Published online 19 March 2025 In the version of the article initially published, in the “Mice” paragraph of the Methods, the text “The mouse sequence for the CNA35-mCherry cassette was obtained from Dr. Rinkevich at Helmholtz Zentrum Munchen” was missing and has now been added. Similarly, the text “Dr. Mück-Häusl and Dr. Rinkevich at Helmholtz Zentrum München for help designing the CNA35-reporter mice” was missing from the Acknowledgements section and has now been added. These corrections have been made to the HTML and PDF versions of the article.
CRIS-Team Scopus Importer:2025-05-16